Au cœur de la réforme des soins de santé mentale en Belgique : les coordinateurs de réseau - Sophie Thunus; Nadège Lorquet (Sociologies, 2014)
This article analyses the Belgian reform of mental health care delivery as a two steps-translation (Callon 1986): the problematization – the devising of a new mental health care model by policy makers, and the interessement – through which “local coordinators” tried to interest local actors to the new model. Based on empirical data, two evidences are stressed: the coordination function is conceived in different ways, ranging from intermediaries to mediators; and the interessement is influenced by systems of concrete action (Friedberg, 1997). Thus, it is argued that in case where translators are appointed to interest local actors to a problematization from the policy arena, their performance is better appraised by considering their commitment to behave as faithful intermediaries or as strategic mediators, and the informal games regulating their system of action.